2021
DOI: 10.1007/s11069-021-05052-6
|View full text |Cite
|
Sign up to set email alerts
|

Urban flood event and associated damage in the Benue valley, Nigeria

Abstract: Flooding events in the Lower Benue valley of Nigeria are often associated with huge damage to properties and loss of life in the adjoining communities. Specific objective of this study is to evaluate the impact of 2017 flood event as typical of the study area. Method used was an integrated environmental approach that combines analysis of rainfall and discharge data with social surveys, remote sensing and geographical information system. Standardized Precipitation Index (SPI), Precipitation Concentration Index … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The Benue region of Nigeria consists of minority ethnic groups whose major occupation is farming and fishing. Due to heavy rainfall swelling the River Benue and neighbouring water bodies like the Niger River and the Lagdo reservoir in Northern Cameroon, Benue has in recent times witnessed major floods (Brooks et al, 2020;Ologunorisa et al, 2022). As a region with extensive arable farmlands and grasslands, it has also experienced recurrent herder-farmer clashes which are now intensifying as a result of CC (Njoku et al, 2023;Vanger & Nwosu, 2020).…”
Section: Violence In Camps and Sheltersmentioning
confidence: 99%
“…The Benue region of Nigeria consists of minority ethnic groups whose major occupation is farming and fishing. Due to heavy rainfall swelling the River Benue and neighbouring water bodies like the Niger River and the Lagdo reservoir in Northern Cameroon, Benue has in recent times witnessed major floods (Brooks et al, 2020;Ologunorisa et al, 2022). As a region with extensive arable farmlands and grasslands, it has also experienced recurrent herder-farmer clashes which are now intensifying as a result of CC (Njoku et al, 2023;Vanger & Nwosu, 2020).…”
Section: Violence In Camps and Sheltersmentioning
confidence: 99%
“…Runoff also appeared to be positively correlated with monthly runoff in both years studied, as both variables fluctuated simultaneously. Existing studies (e.g., Shuster et al, 2005;Singh et al, 2006;Eludoyin et al, 2017) showed that a positive relationship between precipitation and runoff could indicate the importance of overland flow mechanisms (Ologunorisa et al, 2021). Overland flow mechanisms (particularly the infiltration-excess type) are prevalent in various soil and vegetation environments, largely impermeable or loosely vegetated but dry surfaces, riverine wet and vegetated surfaces, and areas characterized by natural or artificial moles or pipes (Beven, 1986;Eludoyin, 2013;Eludoyin et al, 2017).…”
Section: Runoff Characteristicsmentioning
confidence: 99%
“…These vulnerabilities have been further exacerbated by the lack of proper flood management infrastructure and the predominant informal settlement culture in urban areas (Giri et al, 2021). For instance, according to Ologunorisa et al (2021), the 2017 flood event, which inundated communities in Benue, Kogi and Lagos, led to the displacement of more than 100,000 people and the destruction of social infrastructure worth billions of Naira. Another example is the 2022 flood incidence in Kogi, Bayelsa and Enugu State, which displaced about 50,000 residents Disclosure: The authors report there are no conflicting interests to declare.…”
Section: Introductionmentioning
confidence: 99%